Helping Your School-Age Child Develop a Healthy Self-Concept - Millie Ferrer; Anne M. Fugate (EDIS)
A child’s self-concept is her belief about how worthwhile she is. Self-concept is how the child sees herself. It is made up of a sense of belonging and being accepted, a sense of being good, and a sense of being capable of doing things well.  This document is FCS2205, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. Published February 2003.